2013
DOI: 10.4238/2013.march.13.5
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipid abnormalities are not associated with apoB 3' VNTR polymorphism in nephrotic children

Abstract: ABSTRACT. Apolipoprotein B (apoB) gene 3' variable number of tandem repeat (VNTR) is highly variable, and therefore can be an informative marker for associative analysis of lipid metabolism. This is the first report focusing on a possible association of apoB VNTR polymorphism with nephrotic hyperlipidemia. Genomic DNA was extracted from 500 children with primary nephrotic syndrome (PNS) and 500 healthy controls. The apoB genotype was determined by PCR analysis. Allele size distribution followed a unimodal curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The difference might be referred to the population ethnicity or the disease. In China, Hu et al [25] reported that the genotype and allele distributions of ApoB variants in Chinese children with primary nephrotic syndrome were not significantly different from the control volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…The difference might be referred to the population ethnicity or the disease. In China, Hu et al [25] reported that the genotype and allele distributions of ApoB variants in Chinese children with primary nephrotic syndrome were not significantly different from the control volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…The apoB gene polymorphism can affect the plasma TC, LDL and ApoB levels [ 23 ]. Previous studies indicated that Xba I, EcoR I and 3′-VNTR in ApoB gene were associated with lipid metabolism and related diseases [ 24 , 25 ]. However, in the present study, we did not found association of these SNPs in ApoB gene and osteonecrosis.…”
Section: Discussionmentioning
confidence: 99%